Verbs : aspect and causal structure - Croft, William, 1956- (Oxford : Oxford University Press, 2012)
Examining the syntax and semantics of verbs from a crosslinguistic perspective, this book encompasses the full range of English verb classes, has a strong typological dimension and presents a model of event structure that breaks new ground in predicting and explaining linguistic facts.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: Grammar, Comparative and general -- Verb; Grammar, Comparative and general -- Aspect